Układ o Jednym Stopniu Swobody o Silnie Nieliniowej Parzystej Charakterystyce Tłumienia - Bogusz, W.; Szpunar, K. (Engineering Transactions, 1960)
For qualitative investigation the method of the velocity hodograph is used. Analytic investigation is done by means of the method of analysis of the solution in the xx-plane. The results obtained by the two methods are in agreement. It is found that the equation under consideration has periodic solutions in the neighbourhood of the singular points and the solutions outside this region being unbounded. The form of the trajectory is determined in the entire phase plane. Equations for the period of the periodic solutions and the displacement amplitudes are obtained.